The Nigerian economic summit group : The submission to the vision 2010 committee - Nigerian Economic Summit Group (Ibadan : Spectrum, 1997)
The book contains the various reports of the committee of the vision 2010.
usc 10/11/2021
Ref.
Keywords: Nigeria